Papel do transportador OsHMA5 nas respostas de plantas de arroz (Oryza sativa L.) à deficiência e excesso de cobre - Frari, Bianca Knebel Del (2018)
Copper (Cu) is an essential mineral element as a cofactor of many proteins that participate in important physiological processes, such as plastocyanin that acts in the electron transport chain in photochemistry. However, its excess or deficiency may imply several negative effects on cells components. Therefore, the plants need to maintain Cu homeostasis on the cells through different mechanisms. Among them, a mechanism in response to Cu deficiency, known as Cu economy, has already been characterized in Arabidopsis thaliana. Despite of the growing advance in characterization of proteins involved in Cu homeostasis, it is still necessary to understand its relations with important physiological processes, such as photosynthesis, and mechanisms related to Cu tolerance and deficiency in different plant species. In this context, the objective of the present work was to characterize aspects related to Cu homeostasis in Oryza sativa through the role of the OsHMA5 transporter, as well as physiological, morphological and molecular parameters of both wild type (cv. Nipponbare) and oshma5 mutant. The experiment was carried out in a controlled growth room in which wild type (cv. Nipponbare) and oshma5 mutant plants were submitted to three concentrations of Cu (without addition of Cu "0"; 0.2 and 20 μM) in nutrient solution for 13 days. In response to Cu deficiency, wild type plants showed higher expression of the OsCOPT1 Cu transporter and lower photosynthetic parameters of ETR and Y(II), before demonstrating reduction in growth parameters. In addition, the wild type in the Cu deficiency condition showed the same behavior of the oshma5 mutant in the ETR and Y(II) parameters. There was lower concentration of mineral elements (Cu, Fe, Mg and Zn) in the shoot of the oshma5 mutant in 20 μM of Cu compared to the wild type. However, the wild type presented higher concentration of these elements in the shoot of plants submitted to 20 μM of Cu in relation to the other concentrations of Cu. However, both presented lower Mn concentration on root tissues with the Cu increases in the nutrient solution. In addition, the higher concentration of Cu in the nutrient solution caused negative effects on growth parameters (dry matter of roots and shoot, leaf area, length and root surface area) in wild type and oshma5 mutant, evidencing that the transporter OsHMA5 does not contribute significantly to tolerance of Cu excess. In the wild type, the miRNAs analyzed (miRNA397ab, miRNA398b and miRNA408) are induced in Cu deficiency, so it seems that the Cu economy mechanism is conserved in Oryza sativa.